2007
DOI: 10.1021/ic700643n
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen and Copper Ion-Induced Molecular Reorganizations in Scorpionand-like Ligands. A Potentiometric, Mechanistic, and Solid-State Study

Abstract: Two aza scorpionand-like macrocycles (L2 and L3) have been prepared. L2 consists of a tren amine with two of its arms cyclizized with a 2,6-bis(bromomethyl)pyridine. In L3, the remaining pendant arm has been further functionalized with a fluorophoric naphthalene group. X-ray data on the compounds [H(L3)]ClO4.H2O (1) and [H3(L3)](H2PO4)3.H2O (2) as well as solution studies (pH-metry, UV-vis, and fluorescence data) show the movement of the pendant arm as a result of the protonation degree of the macrocycles and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
107
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 55 publications
(132 citation statements)
references
References 69 publications
11
107
2
Order By: Relevance
“…In of the stability constant obtained is even lower than those obtained for related macrocycles in which penta-coordination of the metal ion was ascertained from crystallographic data ([CuL4] 2+ , log K = 20.43; [CuL5] 2+ , log K = 19.65), 8 and it is close to that reported for the Cu 2+ complex of the tetradentate macrocyclic core ([CuL3] 2+ , log K = 17.78), 8 which could be even considered evidence that the secondary nitrogen in the tail does not coordinate. However, it has to be recalled that deriving coordination numbers just from these equilibrium values could be misleading, and actually the crystal structure of the related [MnL2(H 2 O)](ClO 4 ) 2 complex shows a penta-dentate coordination of the ligand with the quinoline ring placed far away from the metal atom.…”
Section: Potentiometric Studies On the Formation Of Cu(ii) Complexescontrasting
confidence: 58%
See 2 more Smart Citations
“…In of the stability constant obtained is even lower than those obtained for related macrocycles in which penta-coordination of the metal ion was ascertained from crystallographic data ([CuL4] 2+ , log K = 20.43; [CuL5] 2+ , log K = 19.65), 8 and it is close to that reported for the Cu 2+ complex of the tetradentate macrocyclic core ([CuL3] 2+ , log K = 17.78), 8 which could be even considered evidence that the secondary nitrogen in the tail does not coordinate. However, it has to be recalled that deriving coordination numbers just from these equilibrium values could be misleading, and actually the crystal structure of the related [MnL2(H 2 O)](ClO 4 ) 2 complex shows a penta-dentate coordination of the ligand with the quinoline ring placed far away from the metal atom.…”
Section: Potentiometric Studies On the Formation Of Cu(ii) Complexescontrasting
confidence: 58%
“…6 Within this topic, we have previously reported the acid-base and Cu 2+ coordination chemistry of a series of ligands built up by linking together a tris(2-aminoethyl)amine unit to the 2,6 positions of a pyridine spacer through methylene groups (L4), and further functionalizing the hanging arm with a 1-methylnaphthyl unit (L5) or with 2-or 3-pycolyl groups (L6 and L7 in Scheme 1). 7,8 It was found that in the case of L5, the folding movement of the arm towards the macrocyclic core could be achieved not only by coordination of Cu 2+ but also by formation of internal hydrogen bonds in the mono-and diprotonated forms of L5. 8 More recently we have reported the synthesis of two closely related ligands, L1 and L2, which differ from L6 and L7 in that pyridine replaces quinoline.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The labels point out the central bond that undergoes torsion for each dihedron. The corresponding Crystallographic Information Files (CIF) can be found in the Supplementary Materials of Reference [8].…”
Section: Conformational Searchmentioning
confidence: 99%
“…The π-π stacking is evidenced by the minimal distance from the pyridine ring to the naphtalene ring equal to 3.26 Å [10]. The corresponding Crystallographic Information Files (CIF) can be found in the Supplementary Materials of Reference [8].…”
Section: Introductionmentioning
confidence: 99%